Constant-temperature phase-change foam with light and flexible shape memory and preparation method of constant-temperature phase-change foam

By using light, flexible shape-memory thermostatic phase-change foam materials and supercritical fluid foaming technology in PCM thermal insulation materials, the problem of leakage of PCM materials during the phase change process and difficulty in filling a large amount of PCM has been solved, and the material has been realized. The flexibility and shape memory properties improve the energy storage effect and intuitively indicate the phase change process.

CN119331356AActive Publication Date: 2025-01-21QINGDAO UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410441615.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-12
Publication Date
2025-01-21
Estimated Expiration
2044-04-12

AI Technical Summary

Technical Problem

Existing PCM insulation materials are prone to leakage during the phase transition process, and it is difficult to fill a large amount of PCM while maintaining low density and uniform pore structures. It is impossible to visually display the phase transition process, affecting control and prediction.

Method used

The constant temperature phase change foam material with quality and flexible shape memory is used to avoid chemical foaming agents through supercritical fluid foam technology. Combined with preferred packaging materials and nuclear agents, the flexible and shape memory characteristics of the material at the phase change temperature are realized , And introduce the process of seeing the intuitive instructions of temperature change powder.

Benefits of technology

Effectively prevent PCM leakage, realize the flexible and shape memory characteristics of the material, broaden the application range, maintain low density and uniform pore structure, improve the energy storage effect, and improve the convenience of use through intuitive instructions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331356A_ABST
    Figure CN119331356A_ABST
Patent Text Reader

Abstract

The invention discloses light and flexible shape-memory constant-temperature phase-change foam and a preparation method thereof, and relates to the technical field of phase-change foam materials, the constant-temperature phase-change foam is prepared from the following components by weight: 100 parts of a packaging material, 50-200 parts of a phase-change material, 10-50 parts of a nucleating agent, 1-3 parts of a vulcanizing agent, and 1-2 parts of an auxiliary vulcanizing agent; 1-2 parts of an activator; 3-5 parts of zinc oxide, 1-3 parts of an anti-aging agent, 0.5-1 part of a scorch retarder and 0.5-2 parts of temperature change powder. The environment-friendly supercritical foaming technology and the fine material design are adopted, PCM leakage is effectively prevented, and environment friendliness and the energy storage effect are guaranteed. The material has excellent flexibility and shape memory characteristics, and is suitable for the fields of building heat preservation, electronic heat dissipation and the like. By optimizing the structure, efficient energy storage and low density are achieved, meanwhile, the temperature change powder is introduced to visually indicate the phase change process, and use convenience is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of phase change foam materials, and in particular to a light, flexible, shape-memory, constant-temperature phase change foam and a preparation method thereof. Background Art

[0002] As the global standards for energy conservation and emission reduction become increasingly stringent, the demand for high-efficiency energy-saving materials in the construction field continues to grow. In particular, the research and development of thermal insulation materials for building exterior walls aims to reduce energy consumption, maintain a constant indoor temperature, and improve the comfort of the living and working environment. Phase change materials (PCM) have become one of the key technologies for improving building energy efficiency due to their unique thermal energy storage and release properties. PCM changes its physical state within a specific temperature range, absorbs or releases a large amount of latent heat, and achieves heat storage and conversion, thereby maintaining a constant temperature state in the environment. However, although PCM technology has great potential in theory, it still faces many technical challenges and limitations in practical applications.

[0003] At present, PCM materials used in the field of building thermal insulation are mainly added to traditional thermal insulation materials. Although these materials have achieved the goals of temperature control and energy storage to a certain extent, there are several problems that cannot be ignored. First, PCM is prone to leakage when undergoing a phase change process, which not only pollutes the environment, but also seriously affects the service life and energy storage effect of the material. Secondly, most of the current PCM thermal insulation materials remain solid at the phase change temperature, which limits the close fit between the material and the surface of the wrapped object, thereby affecting the use effect and application scope. In addition, it is difficult to fill a large amount of PCM to achieve efficient energy storage while maintaining the low density and uniform pore structure of the material in the prior art. Moreover, most materials obtain the pore structure by adding chemical foaming agents. This method is not only environmentally unfriendly, but also leads to uneven pore size distribution, voids and pore breakage. Finally, the prior art cannot intuitively display the phase change process of PCM, making it difficult to control and predict the start and end time of the phase change.

[0004] In view of the limitations of the above-mentioned prior art, the present invention aims to solve a series of problems existing in the application of thermal insulation materials doped with PCM. Specifically, the objectives of the present invention include: (1) developing a new type of phase change foam material, which can effectively prevent the leakage of PCM during the phase change process, ensure environmental friendliness and long-term stable energy storage effect; (2) through innovative material design, realize the flexibility and shape memory characteristics of the material at the phase change temperature, so that the material can better fit various surfaces and broaden its application range; (3) optimize the material structure, realize low density and uniform pore structure while efficiently filling a large amount of PCM, and achieve excellent energy storage effect; (4) adopt environmentally friendly supercritical fluid foaming technology to avoid the use of chemical foaming agents and obtain uniform pore structure; (5) introduce temperature change powder, the color change temperature range of the temperature change powder matches the phase change temperature of the phase change material, so as to intuitively indicate the phase change process and help users accurately grasp the start and end time of the phase change. By solving these technical problems, the present invention intends to provide a more effective, environmentally friendly and reliable solution for the field of building thermal insulation materials. Summary of the invention

[0005] In order to achieve the above-mentioned invention object, in view of the above-mentioned technical problems: The invention provides a light, flexible, shape-memory, thermostatic phase-change foam. The thermostatic phase-change foam is prepared from the following components in parts by weight: 100 parts of packaging material, 50-200 parts of phase-change material, 10-50 parts of nucleating agent, 1-3 parts of vulcanizing agent, 1-2 parts of auxiliary vulcanizing agent, 1-2 parts of activating agent, 3-5 parts of zinc oxide, 1-3 parts of antioxidant, 0.5-1 part of anti-scorching agent and 0.5-2 parts of temperature-change powder.

[0006] Preferably, the packaging material is one or more of natural rubber, styrene-butadiene rubber, butadiene rubber, ethylene-propylene rubber, butyl rubber, and SEBS.

[0007] Preferably, the phase change material is solid paraffin.

[0008] Preferably, the melting point of the solid paraffin is 48-70°C.

[0009] Preferably, the nucleating agent is one of silica aerogel, white carbon black, carbon black, calcium carbonate, nano titanium dioxide, carbon nanotubes and graphene.

[0010] Preferably, the vulcanizing agent is any one of di-tert-butyl peroxyisopropylbenzene, diisopropylbenzene peroxide, 2,4-di-tert-butyl peroxideisopropylbenzene, benzoyl peroxide, dipentadienyl, and sulfur; the co-vulcanizing agent is any one of triallyl isocyanurate, N,N'-m-phenylene bismaleimide, trimethylolpropane methacrylate, and triallyl cyanurate; the activator is stearic acid; the scorch retarder is one of N-cyclohexylthiophthalimide, salicylic acid, phthalic anhydride, and nitroso compounds; the antioxidant is any one of antioxidant RD, antioxidant OD, and antioxidant H, and the temperature-changing powder is one of 40-70°C.

[0011] The present application also provides a method for preparing the above phase change foam, comprising the following steps: S1: Mix the packaging material and the phase change material by melt mixing method, add the nucleating agent after mixing, add the vulcanizing agent, the co-vulcanizing agent, the activator, the zinc oxide, the anti-aging agent, the anti-scorching agent, the temperature change powder after mixing, mix evenly, and obtain the mixed rubber material; S2: the mixed rubber material of step S1 is left for 24 hours, and then subjected to high temperature molding on a flat vulcanizing machine, wherein the vulcanization temperature is set to 140-170° C., and the molding time includes hot pressing and cold pressing to obtain the molded rubber material; S3: supercritically foaming the molded material in step S2 in a foaming kettle, wherein the foaming gas is carbon dioxide, nitrogen or a mixture of the two, the foaming time is 1-3 hours, and the gas pressure is 15-30 MPa to obtain a foamed material; S4: performing secondary high-temperature vulcanization of the foaming material in step S3 in an oven at a vulcanization temperature of 170-200° C. to obtain a phase change foam.

[0012] Preferably, the mixing temperature in step S1 is 80-100° C.; and the hot pressing time in step S2 is 4-10 minutes.

[0013] Preferably, the foaming temperature in step S3 is 60-100°C.

[0014] Preferably, the vulcanization time in step S4 is 20-30 minutes.

[0015] The technical solution provided by the embodiment of the present invention has the following beneficial effects: Effectively prevent PCM leakage: The present invention ensures the stability of phase change materials (such as solid paraffin) during the phase change process through sophisticated material design and preparation technology, effectively prevents PCM leakage during use, and improves environmental friendliness and long-term stable energy storage effect. In particular, the use of supercritical foaming technology avoids the use of chemical foaming agents, which is not only environmentally friendly but also can obtain a more uniform and fine pore structure, further preventing PCM leakage.

[0016] Flexibility and shape memory properties: The phase change foam material of the present invention has excellent flexibility and shape memory properties at the phase change temperature, so that the material can better fit various surface shapes, significantly broadening its application range in the fields of building thermal insulation, electronic product heat dissipation, etc. These properties are achieved through the reasonable combination of preferred packaging materials and nucleating agents, effectively improving the flexibility and practical value of the material.

[0017] Efficient energy storage effect and low-density structure: The present invention optimizes the material structure of the phase change foam, and can maintain a low density and uniform pore structure even when filled with a large amount of PCM, achieving excellent energy storage effect. This is verified by mechanical property tests and scanning electron microscope (SEM) analysis of comparative examples and embodiments, indicating that the material can achieve efficient thermal energy storage and regulation without adding too much weight.

[0018] Environmentally friendly preparation process: The supercritical foaming technology used is more environmentally friendly than the traditional chemical foaming method and can reduce the impact on the environment. In addition, the selected packaging materials and nucleating agents are all environmentally friendly materials, ensuring the green and safety of the entire production process.

[0019] Introduction of temperature-change powder: By introducing temperature-change powder into the phase-change foam material, the phase change process of the material can be intuitively indicated, helping users to accurately grasp the start and end time of the phase change, thereby improving convenience and efficiency during use. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 These are photos of foaming experiments of Example 2 and Comparative Example 3 of the present invention.

[0021] Figure 2 This is the SEM scanning electron microscope image of Comparative Example 1 of the present invention.

[0022] Figure 3 This is a SEM scanning electron microscope image of Example 1 of the present invention.

[0023] Figure 4 This is the SEM scanning electron microscope image of Comparative Example 2 of the present invention.

[0024] Figure 5 This is the SEM scanning electron microscope image of Comparative Example 4 of the present invention.

[0025] Figure 6 This is a SEM scanning electron microscope image of Example 2 of the present invention.

[0026] Figure 7 This is the SEM scanning electron microscope image of Example 3 of the present invention.

[0027] Figure 8 This is the SEM scanning electron microscope image of Example 4 of the present invention.

[0028] Fig. 9 This is the SEM scanning electron microscope image of Example 5 of the present invention.

[0029] Fig.10 This is the SEM scanning electron microscope image of Example 6 of the present invention.

[0030] Fig.11 This is the SEM scanning electron microscope image of Example 7 of the present invention.

[0031] Fig.12 This is the SEM scanning electron microscope image of Example 8 of the present invention.

[0032] Fig.13 This is the SEM scanning electron microscope image of Example 9 of the present invention.

[0033] Fig.14 This is a SEM scanning electron microscope image of Example 10 of the present invention.

[0034] Fig.15 This is the SEM scanning electron microscope image of Example 11 of the present invention.

[0035] Fig.16 This is the SEM scanning electron microscope image of Example 12 of the present invention.

[0036] Fig.17 These are photos of the paraffin leakage experiment of Example 2 of the present invention and Comparative Example 3.

[0037] Fig.18 It is a density curve diagram of Example 2 of the present invention and Comparative Example 3.

[0038] Fig.19 It is a quality curve diagram of Example 2 of the present invention and Comparative Example 3.

[0039] Fig. 20 This is the SEM scanning electron microscope image of Example 13 of the present invention.

[0040] Fig.21 This is the SEM scanning electron microscope image of Example 14 of the present invention.

[0041] Fig. 22 This is the SEM scanning electron microscope image of Example 15 of the present invention.

[0042] Fig.23 This is the SEM scanning electron microscope image of Example 16 of the present invention.

[0043] Fig.24 This is the SEM scanning electron microscope image of Example 17 of the present invention.

[0044] Fig.25 This is the SEM scanning electron microscope image of Example 18 of the present invention.

[0045] Fig.26 This is the color change process of the material during the phase change process of the present invention.

[0046] Fig. 27 This is a photo of the shape memory conformability of the present invention.

[0047] Fig.28 This is a schematic diagram of the shape memory test of the present invention. DETAILED DESCRIPTION

[0048] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0049] Example 1 A method for preparing a lightweight, flexible, shape-memory, thermostatic phase-change foam comprises the following steps: S1: 100 parts of ethylene propylene rubber and 50 parts of solid paraffin with a melting point of 56°C are mixed by melt mixing, the mixing temperature is 80°C, and the rotor speed is 60 rpm; then the rotor speed is reduced to 30 rpm, 10 parts of silica aerogel are added, and the rotor speed is adjusted to 60 rpm, and mixed for 2 minutes; then 2 parts of di-tert-butyl peroxyisopropylbenzene, 1 part of triallyl isocyanurate, 1 part of stearic acid, 5 parts of zinc oxide, 2 parts of antioxidant OD, 0.5 parts of N-cyclohexylthiophthalimide, and 1 part of 56°C temperature-changing powder (the temperature-changing powder is commercially available and purchased from Qingdao Chongyu) are added, and mixed for 4 minutes to obtain a mixed rubber material; S2: the mixed rubber material of step S1 is left for 24 hours, and then subjected to high temperature molding on a flat vulcanizing machine, the vulcanization temperature is set to 160° C., the molding time includes hot pressing for 5 minutes and cold pressing for 4 minutes to obtain the molded rubber material; S3: the molded material of step S2 is subjected to supercritical CO2 foaming in a foaming kettle, the foaming time is 1 hour, the foaming temperature is 60° C., and the gas pressure is 17 MPa to obtain a foamed material; S4: The foaming material of step S3 is subjected to secondary high-temperature vulcanization in an oven at a vulcanization temperature of 170° C. for 20 minutes to obtain a phase change foam.

[0050] Example 2 The preparation was carried out in the same manner as in Example 1, except that the amount of solid paraffin was 100 parts and the hot pressing time was 6 minutes.

[0051] Example 3 The same preparation method as in Example 2 was used, except that the solid paraffin was 150 parts.

[0052] Example 4 The preparation was carried out in the same manner as in Example 1, except that the amount of solid paraffin was 200 parts and the hot pressing time was 8 minutes.

[0053] Example 5 The preparation was carried out in the same manner as in Example 3, except that the amount of silica aerogel was 20 parts.

[0054] Example 6 The preparation was carried out in the same manner as in Example 5, except that the amount of silica aerogel was 30 parts and the curing time was 15 minutes.

[0055] Example 7 The preparation was carried out in the same manner as in Example 5, except that the amount of silica aerogel was 40 parts, the hot pressing time was 4 minutes, and the vulcanization time was 10 minutes.

[0056] Example 8 The preparation was carried out in the same manner as in Example 5, except that the amount of silica aerogel was 50 parts, the hot pressing time was 5 minutes, and the vulcanization time was 10 minutes.

[0057] Example 9 A method for preparing a lightweight, flexible, shape-memory, thermostatic phase-change foam comprises the following steps: S1: 100 parts of natural rubber and 100 parts of solid paraffin with a melting point of 68°C are mixed by melt mixing, the mixing temperature is 80°C, and the rotor speed is 60 rpm; then the rotor speed is reduced to 30 rpm, 10 parts of silica aerogel are added, and the rotor speed is adjusted to 60 rpm, and mixed for 2 minutes; then 3 parts of sulfur, 2 parts of accelerator TMTD, 2 parts of stearic acid, 4 parts of zinc oxide, 3 parts of antioxidant OD, 1 part of N-cyclohexylthiophthalimide, and 1 part of 68°C temperature-changing powder (the temperature-changing powder is commercially available and purchased from Qingdao Chongyu) are added, and mixed for 4 minutes to obtain a mixed rubber material; S2: the mixed rubber material of step S1 is left for 24 hours, and then subjected to high temperature molding on a flat vulcanizing machine, the vulcanization temperature is set to 160° C., the molding time includes hot pressing for 4 minutes and cold pressing for 4 minutes to obtain a molded rubber material; S3: the molding material of step S2 is subjected to supercritical N2 foaming in a foaming kettle, the foaming time is 2 hours, the foaming temperature is 80° C., and the gas pressure is 30 MPa to obtain a foamed material; S4: The foaming material of step S3 is subjected to secondary high-temperature vulcanization in an oven at a vulcanization temperature of 170° C. for 20 minutes to obtain a phase change foam.

[0058] Example 10 A method for preparing a lightweight, flexible, shape-memory, thermostatic phase-change foam comprises the following steps: S1: 80 / 20 parts of styrene-butadiene rubber / butadiene rubber and 100 parts of solid paraffin with a melting point of 60°C are mixed by melt mixing, the mixing temperature is 80°C, and the rotor speed is 60 rpm; then the rotor speed is reduced to 30 rpm, 10 parts of silica aerogel are added, and the rotor speed is adjusted to 60 rpm, and mixed for 2 minutes; then 1.5 parts of sulfur, 1 part of N-tert-butyl-2-benzothiazole sulfonamide (TBBS), 1.5 parts of stearic acid, 3 parts of zinc oxide, 3 parts of antioxidant H, 1 part of N-cyclohexylthiophthalimide, and 1 part of 60°C temperature-changing powder (the temperature-changing powder is commercially available and purchased from Qingdao Chongyu) are added, and mixed for 4 minutes to obtain a mixed rubber material; S2: the mixed rubber material of step S1 is left for 24 hours, and then subjected to high temperature molding on a flat vulcanizing machine, the vulcanization temperature is set to 160° C., the molding time includes hot pressing for 4 minutes and cold pressing for 4 minutes to obtain a molded rubber material; S3: supercritically foaming the molded material in step S2 in a foaming kettle, with the foaming gas being 4MPaCO2+20MPaN2, the foaming time being 2 hours, the foaming temperature being 100°C, and the gas pressure being 24MPa to obtain a foamed material; S4: The foaming material of step S3 is subjected to secondary high-temperature vulcanization in an oven at a vulcanization temperature of 180° C. for 15 minutes to obtain a phase change foam.

[0059] Embodiment 11 A method for preparing a lightweight, flexible, shape-memory, thermostatic phase-change foam comprises the following steps: S1: 70 / 30 parts of butyl rubber / natural rubber and 100 parts of solid paraffin with a melting point of 66°C are mixed by melt mixing, the mixing temperature is 80°C, and the rotor speed is 60 rpm; then the rotor speed is reduced to 30 rpm, 10 parts of silica aerogel are added, and the rotor speed is adjusted to 60 rpm, and mixed for 2 minutes; then 2 parts of sulfur, 2 parts of accelerator DM, 2 parts of stearic acid, 4 parts of zinc oxide, 1.5 parts of antioxidant RD, 1 part of N-cyclohexylthiophthalimide, and 1 part of 66°C temperature-changing powder (the temperature-changing powder is commercially available and purchased from Qingdao Chongyu) are added, and mixed for 4 minutes to obtain a mixed rubber material; S2: the mixed rubber material of step S1 is left for 24 hours, and then subjected to high temperature molding on a flat vulcanizing machine, the vulcanization temperature is set to 160° C., the molding time includes hot pressing for 4 minutes and cold pressing for 4 minutes to obtain a molded rubber material; S3: subjecting the molded material of step S2 to supercritical CO2 foaming in a foaming kettle, with a foaming time of 2 hours, a foaming temperature of 100° C., and a gas pressure of 17 MPa to obtain a foamed material; S4: The foaming material of step S3 is subjected to secondary high-temperature vulcanization in an oven at a vulcanization temperature of 170° C. for 20 minutes to obtain a phase change foam.

[0060] Example 12 A method for preparing a lightweight, flexible, shape-memory, thermostatic phase-change foam comprises the following steps: S1: 100 parts of SEBS and 150 parts of solid paraffin with a melting point of 70°C were mixed by melt mixing, the mixing temperature was 100°C, and the rotor speed was 60 rpm; then the rotor speed was reduced to 30 rpm, 10 parts of silica aerogel were added, and the rotor speed was adjusted to 60 rpm, and mixed for 2 minutes; then 1 part of diisopropylbenzene peroxide (DCP), 1 part of triallyl isocyanurate (TAIC), 1 part of stearic acid, 3 parts of zinc oxide, 2 parts of antioxidant OD, 0.5 part of N-cyclohexylthiophthalimide, and 1 part of 70°C temperature-changing powder (the temperature-changing powder is commercially available and purchased from Qingdao Chongyu) were added, and mixed for 4 minutes to obtain a mixed rubber material; S2: the mixed rubber material of step S1 is left for 24 hours, and then subjected to high temperature molding on a flat vulcanizing machine, the vulcanization temperature is set to 160° C., the molding time includes hot pressing for 8 minutes and cold pressing for 4 minutes to obtain a molded rubber material; S3: foaming the molded material in step S2 with supercritical N2 in a foaming kettle for 2 hours at a foaming temperature of 80° C. and a gas pressure of 25 MPa to obtain a foamed material; S4: performing secondary high-temperature vulcanization of the foaming material in step S3 in an oven at a vulcanization temperature of 200° C. for 10 minutes to obtain a phase change foam.

[0061] Example 13 The preparation was carried out in the same manner as in Example 2, except that the nucleating agent was graphene, the mixing temperature was 80° C., and the vulcanization time was 20 minutes.

[0062] Embodiment 14 The same preparation method as that of Example 13 was used, except that the nucleating agent was carbon black N330.

[0063] Embodiment 15 The method is the same as that of Example 13, except that the nucleating agent is nano titanium dioxide.

[0064] Example 16 The preparation was carried out in the same manner as in Example 13, except that the nucleating agent was calcium carbonate.

[0065] Embodiment 17 The preparation was carried out in the same manner as in Example 13, except that the nucleating agent was fumed silica.

[0066] Embodiment 18 The preparation is carried out in the same manner as in Example 13, except that the nucleating agent is carbon nanotubes.

[0067] Implementation 19 A method for preparing a lightweight, flexible, shape-memory, thermostatic phase-change foam comprises the following steps: S1: 100 parts of ethylene propylene rubber and 50 parts of solid paraffin with a melting point of 48°C are mixed by melt mixing, the mixing temperature is 80°C, and the rotor speed is 60 rpm; then the rotor speed is reduced to 30 rpm, 10 parts of silica aerogel are added, and the rotor speed is adjusted to 60 rpm, and mixed for 2 minutes; then 1 part of di-tert-butyl peroxyisopropylbenzene, 1 part of triallyl isocyanurate, 1 part of stearic acid, 3 parts of zinc oxide, 1 part of antioxidant OD, 0.5 part of N-cyclohexylthiophthalimide, and 0.5 part of 40°C temperature-changing powder (the temperature-changing powder is commercially available and purchased from Qingdao Chongyu) are added, and mixed for 4 minutes to obtain a mixed rubber material; S2: the mixed rubber material of step S1 is left for 24 hours, and then subjected to high temperature molding on a flat vulcanizing machine, the vulcanization temperature is set to 140° C., the molding time includes hot pressing for 5 minutes and cold pressing for 4 minutes to obtain the molded rubber material; S3: subjecting the molded material of step S2 to supercritical CO2 foaming in a foaming kettle, with a foaming time of 1 hour, a foaming temperature of 60° C., and a gas pressure of 15 MPa to obtain a foamed material; S4: The foaming material of step S3 is subjected to secondary high-temperature vulcanization in an oven at a vulcanization temperature of 170° C. for 20 minutes to obtain a phase change foam.

[0068] Implementation 20 A method for preparing a lightweight, flexible, shape-memory, thermostatic phase-change foam comprises the following steps: S1: 100 parts of ethylene propylene rubber and 200 parts of solid paraffin with a melting point of 70°C are mixed by melt mixing, the mixing temperature is 100°C, and the rotor speed is 60 rpm; then the rotor speed is reduced to 30 rpm, 50 parts of silica aerogel are added, and the rotor speed is adjusted to 60 rpm, and mixed for 2 minutes; then 3 parts of di-tert-butyl peroxyisopropylbenzene, 2 parts of triallyl isocyanurate, 2 parts of stearic acid, 5 parts of zinc oxide, 3 parts of antioxidant OD, 1 part of N-cyclohexylthiophthalimide, and 2 parts of 70°C temperature-changing powder (the temperature-changing powder is commercially available and purchased from Qingdao Chongyu) are added, and mixed for 4 minutes to obtain a mixed rubber material; S2: the mixed rubber material of step S1 is left for 24 hours, and then subjected to high temperature molding on a flat vulcanizing machine, the vulcanization temperature is set to 170° C., the molding time includes hot pressing for 10 minutes and cold pressing for 4 minutes to obtain a molded rubber material; S3: subjecting the molded material of step S2 to supercritical CO2 foaming in a foaming kettle, with a foaming time of 3 hours, a foaming temperature of 100° C., and a gas pressure of 30 MPa to obtain a foamed material; S4: performing secondary high-temperature vulcanization of the foaming material in step S3 in an oven, wherein the vulcanization temperature is 200° C. and the vulcanization time is 30 minutes to obtain a phase change foam.

[0069] Comparative Example 1 The same preparation method as in Example 1 was used for the preparation, except that no solid paraffin was added and the hot pressing time was 4 minutes.

[0070] Comparative Example 2 The preparation was carried out in the same manner as in Example 3, except that no carbon dioxide aerogel was added.

[0071] Comparative Example 3 A method for preparing a lightweight, flexible, shape-memory, thermostatic phase-change foam comprises the following steps: S1 Set the temperature of the internal mixer to 80℃. After the temperature stabilizes, add 100 parts of EPDM and 150 parts of PW with a melting point of 56℃ in sequence. After mixing evenly, add the vulcanization system (1 part of stearic acid (SA), 5 parts of zinc oxide (ZnO), 2 parts of di-tert-butyl peroxide isopropylbenzene (BIPB), 1 part of triallyl isocyanurate (TAIC)), 1 part of temperature-dependent powder, 1 part of scorch retarder N-cyclohexylthiophthalimide (PVI or CTP), 15 parts of azodicarbonamide (AC), and 1 part of antioxidant OD to obtain a mixed rubber; S2: putting the rubber mixture obtained in step S1 into an open mixer, pressing it into thin sheets through the open mixer, and cutting it to obtain a pressed test piece; S3: placing the pressed test piece obtained in step S2 into a mold, and pressing it with a flat vulcanizer for 10 minutes at a temperature of 160° C. and a pressure of 10 MPa to obtain a chemical foaming sample; S4: Put the foamed sample obtained in step S3 into an oven and perform secondary high-temperature vulcanization at 170° C. for 20 minutes to obtain EPDM / PW phase change foam.

[0072] Experimental test: 1. Shape memory test The specific experimental process is as follows: (I) heat the sample in an oven at 90°C; (II) maintain the temperature for 30 min to promote complete melting of the solid paraffin; (III) bend the sample at 90 degrees; (IV) cool to room temperature under constant external force; (V) remove the external force and record the angle , kept at room temperature for 2 h to allow the solid paraffin to solidify, (VI) reheated at 90 °C to promote shape recovery, and the angle was recorded .

[0073] Shape fixation rate: SF (%) = [(90-α) / 90] × 100 Shape recovery rate: SF (%) = (β / 90) × 100 2. Paraffin wax leakage test: The samples of the embodiments and comparative examples were placed on white paper and kept in an oven at 90°C for 72 hours. Every 2 hours, the samples were taken out, their masses were measured on an analytical balance, their densities were measured on a densitometer (GT-XB320M), and the residues on the white paper were observed.

[0074] Table 1 Mechanical properties test

[0075] The above data and SEM images show that as the amount of silica aerogel increases, the density, hardness, tensile strength and tear strength of the phase change foam are improved, while the thermal conductivity decreases and the average cell size decreases, thereby improving the thermal insulation, mechanical properties and structural properties of the foam. These improvements show that by adjusting the amount of silica aerogel added, the performance of the phase change foam can be effectively adjusted to meet different application requirements.

[0076] Table 2 Mechanical properties test

[0077] From the above comparative examples and embodiments, Figure 20-25 It can be seen that the type of nucleating agent has a significant effect on the physical properties of phase change foams, especially in improving tear strength and adjusting tensile strength. Although the changes in density and hardness are not significant, the nucleating agent has a significant effect on the microstructure and thermal transfer properties of the material. Selecting the appropriate nucleating agent and optimizing its dosage are essential to achieving specific material performance goals. These findings highlight the potential of materials science in optimizing the macroscopic properties of materials through microstructural regulation.

[0078] Table 3 Effect of different amounts of solid paraffin wax on shape memory

[0079] As can be seen from the table, the amount of solid paraffin added has a significant effect on the shape memory function of the phase change foam material. Comparative Example 1 without the addition of solid paraffin shows the lowest shape fixation rate and shape recovery rate, which indicates that it has almost no shape memory function. As the proportion of solid paraffin increases, the shape memory function is gradually enhanced, and Examples 2 and 3 achieve the best shape memory performance, i.e., 100% shape fixation rate and recovery rate, after adding a sufficient proportion of solid paraffin. These results clearly point out the importance of the proportion of solid paraffin to improving the shape memory performance of the phase change foam material.

[0080] Figure 17-19 This is a leakage test diagram of solid paraffin. During the test, the mass and density of the phase change foam of Example 2 did not change, while the volume of the phase change foam of Comparative Example 3 shrank visibly, and there was obvious solid paraffin residue on the white paper. Figure 1 It can be seen that the EPDM / PW phase change foam with AC as the foaming agent has a yellowing surface, cracks and bulges. The SEM image shows that the pore structure of the sample is irregular, with perforation and collapse.

[0081] It can be seen from the SEM images of Examples 2, 3 and Examples 9-12 that, in these different packaging materials, a fine pore structure can be obtained through the packaging technology of this solution, achieving a low density and uniform pore structure while maintaining a large amount of PCM phase change material filling.

[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A lightweight, flexible, shape-memory, thermostatic phase-change foam, characterized in that: The constant temperature phase change foam is prepared from the following components in parts by weight: 100 parts of packaging material, 50-200 parts of phase change material, 10-50 parts of nucleating agent, 1-3 parts of vulcanizing agent, 1-2 parts of auxiliary vulcanizing agent, 1-2 parts of activating agent, 3-5 parts of zinc oxide, 1-3 parts of antioxidant, 0.5-1 parts of anti-scorching agent and 0.5-2 parts of temperature change powder.

2. The phase change foam according to claim 1, characterized in that The packaging material is one or more of natural rubber, styrene-butadiene rubber, butadiene rubber, ethylene-propylene rubber, butyl rubber, and SEBS.

3. The phase change foam according to claim 1, characterized in that: The phase change material is solid paraffin.

4. The phase change foam according to claim 3, characterized in that: The melting point of the solid paraffin is 48-70°C.

5. The phase change foam according to claim 1, characterized in that: The nucleating agent is one of silica aerogel, white carbon black, carbon black, calcium carbonate, nano titanium dioxide, carbon nanotubes and graphene.

6. The phase change foam according to claim 1, characterized in that: The vulcanizing agent is any one of di-tert-butyl peroxyisopropylbenzene, diisopropylbenzene peroxide, 2,4-di-tert-butyl peroxideisopropylbenzene, benzoyl peroxide, dipentadienyl, and sulfur; the co-vulcanizing agent is any one of triallyl isocyanurate, N,N'-m-phenylene bismaleimide, trimethylolpropane methacrylate, and triallyl cyanurate; the activator is stearic acid; the scorch retarder is one of N-cyclohexylthiophthalimide, salicylic acid, phthalic anhydride, and nitroso compounds; the antioxidant is any one of antioxidant RD, antioxidant OD, and antioxidant H, and the temperature-changing powder is one of 40-70°C.

7. A method for preparing the phase change foam according to any one of claims 1 to 6, comprising the following steps: S1: Mix the packaging material and the phase change material by melt mixing method, add the nucleating agent after mixing, add the vulcanizing agent, the co-vulcanizing agent, the activator, the zinc oxide, the anti-aging agent, the anti-scorching agent, the temperature change powder after mixing, mix evenly, and obtain the mixed rubber material; S2: the mixed rubber material of step S1 is left for 24 hours, and then subjected to high temperature molding on a flat vulcanizing machine, wherein the vulcanization temperature is set to 140-170° C., and the molding time includes hot pressing and cold pressing to obtain the molded rubber material; S3: supercritically foaming the molded material in step S2 in a foaming kettle, wherein the foaming gas is carbon dioxide, nitrogen or a mixture of the two, the foaming time is 1-3 hours, and the gas pressure is 15-30 MPa to obtain a foamed material; S4: performing secondary high-temperature vulcanization of the foaming material in step S3 in an oven at a vulcanization temperature of 170-200° C. to obtain a phase change foam.

8. The preparation method according to claim 7, characterized in that: The mixing temperature in step S1 is 80-100° C.; the hot pressing time in step S2 is 4-10 minutes.

9. The preparation method according to claim 7, characterized in that: The foaming temperature in step S3 is 60-100°C.

10. The preparation method according to claim 7, characterized in that: The vulcanization time in step S4 is 20-30 minutes.

Citation Information

Patent Citations

  • Phase change material and preparation method and application thereof

    CN111777817A

  • Brominated butyl rubber / polyethylene thermal insulation buffer material and preparation process thereof

    CN116554533A

  • Composite foam and methods of preparation and use

    US20170072604A1

  • Insulating Plastic Foams Based On Polyolefins

    US20180291166A1